Mesh complications: best practice in diagnosis and treatment. (July 2020) - Bueno Garcia Reyes, Paulina; Hashim, Hashim
Mesh was a promising, minimally invasive, and 'gold standard' treatment for urinary stress incontinence. Time has shown that complications from these devices can happen early, or even several years, after mesh placement and can be catastrophic. Pain, erosion, voiding dysfunction, infection, recurrent UTIs [urinary tract infections (UTIs)], fistulae, organ perforation, bleeding, vaginal scarring, neuromuscular alterations, LUTS (lower urinary tract symptoms), bowel complications and even immune disorders have been linked to mesh. Various tools, such as imaging, endoscopic and functional studies, are available for diagnosis of mesh complications. Since the spectrum of complications is wide, involvement of other specialties is usually beneficial in the diagnosis and management of these complications. There is still much to learn on the accuracy and utility of diagnostic studies in each type of complication. Evidence on the best diagnostic and treatment pathways for these complications is scarce but continuously growing as information is being reported, and we continue to gain expertise in dealing with patients affected by mesh. Treatment options include conservative and medical management initially and then open or minimally invasive surgical procedure approaches. This article will describe diagnostic and treatment pathways for mesh complications.